Cultivar Mixture: Old but Impactful Plant Disease Management Strategy - Kumar, Gagan; Rashid, Md. Mahtab; Teli, Basavaraj; Bajpai, Raina; Nanda, Satyabrata; Yadav, Sudheer Kumar (International Journal of Economic Plants, 2021)
The two most commonly used disease management methods prevalent in agricultural package of practices are: the application of chemicals and the selection of disease-resistant cultivars through the introduction of resistance genes. Each of these preventive measures are equally susceptible to the adaptations of phytopathogens in due course of time. There are numerous records of several phytopathogens overcomimg the resistance provided by the main resistance gene through continuous evolution. In a similar fashion, the development and fixation of pesticides resistance mutations in the phytopathogens has made many pesticides to lose their effectiveness. The existingdisease management practices are presumably deficient in supporting the sustainable intensification of crop productivity due to its inadequacy of minimizing the phytopathogen evolution. Thus, comes the role of cultivar mixture which is based on the principle of supressing the evolution of phytopathogen against a specific gene or pesticide. Combinations of cultivars having several different characteristics but sufficient morphological and physiological similarities can be cultivated collectively.These cultivar mixtures do not cause any significant changes in crop production system, yet improve the yield accuracy, and decrease the use of pesticides in many cases. They are also faster and cheaper to develop and are distinctive to “multiline” which are identified as combinations of genetically identical lines of a crop species varying mostly in disease resistance gene. The use of cultivar mixtures can improve the effectiveness of disease management practices as their level of resistance vary in the same region.